Pengaruh Teamwork Dan Team Engagement Melalui Job Distress Terhadap Produktifitas Sales Otomotif Mobil Aceh Barat - Marzuki Marzuki (INDO PUBLISHING, 2026)
This study aims to analyze the influence of teamwork, team engagement, and job distress on employee productivity in the automotive industry in West Aceh, as well as examine the mediating role of job distress. The research employed a quantitative explanatory approach, involving 70 automotive sales respondents. Data were analyzed using Partial Least Square – Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results show that teamwork has a positive and significant effect on productivity, with a T-statistic value of 22.847 and a P-value of 0.000, indicating that teamwork is the most dominant factor in enhancing productivity. In contrast, team engagement does not significantly affect productivity, as reflected by a T-statistic of 1.862 and a P-value of 0.066. Regarding job distress, both teamwork (T-statistic 3.058, P-value 0.003) and team engagement (T-statistic 6.704, P-value 0.000) were found to have a positive and significant effect, meaning that higher teamwork dynamics and team involvement tend to increase psychological pressure among employees. Furthermore, job distress has a negative and significant effect on productivity, with a T-statistic of 1.997 and a P-value of 0.049, indicating that higher distress leads to lower productivity. The mediation analysis reveals that job distress does not mediate the relationship between teamwork and productivity (T-statistic 1.394, P-value 0.166), but significantly mediates the relationship between team engagement and productivity (T-statistic 2.003, P-value 0.048). Overall, the findings highlight the importance of strengthening teamwork to boost productivity, while also emphasizing the need to manage job distress to prevent psychological pressure from hindering employee performance in the automotive sales sector of West Aceh.